2014
DOI: 10.1590/s0036-46652014000500002
|View full text |Cite
|
Sign up to set email alerts
|

Montenegro Skin Test and Age of Skin Lesion as Predictors of Treatment Failure in Cutaneous Leishmaniasis

Abstract: A case-control study was conducted to examine the association among the Montenegro skin test (MST), age of skin lesion and therapeutic response in patients with cutaneous leishmaniasis (CL) treated at Evandro Chagas National Institute of Infectious Diseases (INI), Oswaldo Cruz Foundation (FIOCRUZ), Rio de Janeiro, Brazil. For each treatment failure (case), two controls showing skin lesion healing following treatment, paired by sex and age, were randomly selected. All patients were treated with 5 mg Sb5+/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
1
24
0
2
Order By: Relevance
“…Based on these observations, MA 5 mg Sb v /kg/day IM or IV was successfully administered in up to three 10-day series interspersed with 10-day periods without medication for CL treatment in patients above 60 years, those with comorbidities, or after discontinuation of systemic treatment due to adverse effects 22 . In different series of cases of CL 18,19,20,23 or ML 20 patients treated with 5 mg Sb v /kg / day MA, the frequency of successful treatment varied between 80 and 86%. These responses were similar to the efficacy of 76.5% reported for the conventional dose of 20 mg Sb v / kg / day 9 , but with a lower frequency of adverse effects 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on these observations, MA 5 mg Sb v /kg/day IM or IV was successfully administered in up to three 10-day series interspersed with 10-day periods without medication for CL treatment in patients above 60 years, those with comorbidities, or after discontinuation of systemic treatment due to adverse effects 22 . In different series of cases of CL 18,19,20,23 or ML 20 patients treated with 5 mg Sb v /kg / day MA, the frequency of successful treatment varied between 80 and 86%. These responses were similar to the efficacy of 76.5% reported for the conventional dose of 20 mg Sb v / kg / day 9 , but with a lower frequency of adverse effects 24 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that early treatment of ACL does not prevent the development of ulcers [25, 26] and is associated with higher treatment failure rates [26]. Short evolution times prior to treatment and weak positive MST were both associated with treatment failure [27]. Other factors have also been found to be able to influence the therapeutic response to PA.…”
Section: Discussionmentioning
confidence: 99%
“…Nine (1.2%) patients and 11 (1.4%) patients with lesion durations >2 months presented negative MST results, depending on the cut-off (5mm and 6mm, respectively). A negative response with the MST after 2 months of disease evolution might be related with a defect of the host immune response (23) . The ROC curves that were constructed according to sex showed higher sensitivity for men, which supports the fi ndings of a previous study (26) , while higher specifi city was found for women for both cut-off points.…”
Section: A B C Dmentioning
confidence: 99%